An algorithm for the management of traumatic abdominal wall hernia based on a 9‐year review. Issue 10 (1st September 2022) - Wong, Jessica; Peng, Calvin; Shakerian, Rose; Knowles, Brett; Thomson, Ben; Read, David J.
Abstract: Background: Traumatic abdominal wall hernia (TAWH) is a rare consequence of blunt abdominal trauma, usually in the setting of multitrauma, with little consensus or guidelines for management. We present a case series of patients with traumatic herniae over a 9‐year period and a suggested management algorithm. Method: Retrospective review of all patients with TAWH from 1st January 2011 to 31st December 2019 at a Level 1 adult Major Trauma Centre. Clinical presentation, surgical intervention and complications and recurrence were analysed. Results: Forty‐seven patients were found to have TAWH, 0.5% of all major trauma admissions. Thirty (63.8%) were repaired, 12 acutely, 11 semi‐acute and 7 delayed. All but 1 (fall>3 m) were transport associated, with a median Injury Severity Score (ISS) of 29. Follow‐up data for operative cases were available for all but one (97%). Seven (23.3%) cases had a recurrence, more common in the acute repair group (33.3%) compared to semi‐acute (18.2%), and elective group (14.3%). Conclusion: TAWH is a rare but potentially serious consequence of blunt abdominal trauma. This series has favoured earlier repair for anterior TAWH, or all those undergoing a laparotomy for other reasons, and elective repair for lumbar or lateral TAWH that do not require a laparotomy for other conditions. We present our preferred algorithm for management, accepting that there are many available strategies in this heterogeneous group of injuries. Loss of follow up and recurrence are a concern, and clinicians are encouraged to develop processes to ensure that TAWH are not a 'forgotten hernia'. Abstract : Traumatic abdominal wall hernia is a rare but potentially serious consequence of blunt abdominal trauma. We present a case series of patients with traumatic herniae over a 9‐year period and a suggested management algorithm.